1983
DOI: 10.1126/science.6403984
|View full text |Cite
|
Sign up to set email alerts
|

Cloned Fragment A of Diphtheria Toxin Is Expressed and Secreted into the Periplasmic Space of Escherichia coli K12

Abstract: An 831-base pair segment of the corynebacteriophage beta tox-45 genome encoding fragment A of diphtheria toxin was cloned into plasmid pUC8 in Escherichia coli K12. Strains containing recombinant plasmids expressed the adenosine diphosphate ribosyl transferase activity characteristic of fragment A; this activity could be inhibited by polyvalent antiserum to fragment A as well as by the appropriate monoclonal antibodies to diphtheria toxin. The transferase activity was secreted into the periplasmic space of E. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…Because the three proteolytically sensitive arginines present in the Cys186-Cys20, disulfide loop of the toxin were also present in this fragment, the doublet probably arises from partial cleavage at one of these sites to yield fragment A alone. This cleavage reaction has been well demonstrated with the pDT201 protein in vitro (31).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Because the three proteolytically sensitive arginines present in the Cys186-Cys20, disulfide loop of the toxin were also present in this fragment, the doublet probably arises from partial cleavage at one of these sites to yield fragment A alone. This cleavage reaction has been well demonstrated with the pDT201 protein in vitro (31).…”
Section: Resultsmentioning
confidence: 92%
“…The expression of genes for fragment A in E. coli gives a stable, active protein (31). In marked contrast, our genes coding for proteins composed of fragment A plus 97, 184, or 292 amino acids of fragment B give many intermediatelength polypeptides, in addition to the full-length species, upon expression in E. coli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we observed the same results with sonic extracts or lysozyme-EDTA-treated cells carrying pABM1508 (PR driven, periplasmic). This observation was a surprise since we (35) and others (54) had shown that fragment A alone is expressed and secreted to the periplasmic space in a soluble form.…”
Section: Fig 3 Westem Blot Analysismentioning
confidence: 84%
“…The C. diphtheriae tox 176 lysogen was grown and lysed after penicillin treatment (15), and chromosomal DNA was isolated. To detect the tox 176 sequence, restriction digests of the DNA were subjected to Southern hybridization (16) by using a probe derived from the wild-type DT-A coding sequence, subcloned from pDT201 (10). This analysis (data not shown) revealed a single hybridizing band of ca.…”
mentioning
confidence: 99%